The Use of Mockup Media to Improve Explanatory Text Writing Skills for Class IX SMP Negeri 4 Gunungputri, Bogor Regency - Atikoh, Ummul Badriah; Ganeswara, M. Ginanjar (Journal of English Language and Education, 2025)
This study aims to determine the improvement in the writing skills of explanatory texts of ninth-grade students at SMP Negeri 4 Gunungputri, Bogor Regency, using mock-ups. The problem raised is the lack of writing practice, which results in low mastery of basic skills such as vocabulary and the ability to organize ideas logically. In addition, the limited learning media in the classroom also becomes an obstacle, because students do not get a variety of media that can help them focus on learning to write, so that understanding of concepts in the learning process is also low. This study uses a quantitative approach with an experimental research method in the form of a quasi-experimental design. The population in this study were all ninth-grade students of SMP Negeri 4 Gunungputri, Bogor Regency, which consists of 7 classes. Therefore, the researcher took a sample from the population by involving a number of ninth-grade students. In this study, the population taken was ninth-grade students. Data collection techniques used in this study were test techniques in the form of written tests and non-test techniques in the form of questionnaires. Data analysis was carried out using validity tests, reliability tests, and t-tests. The results showed that the average score of the experimental class increased by 18.43 points (from 52.21 to 70.64), while the average score of the control class increased by 12.86 points (from 47.64 to 60.5). This indicates that the use of mockups is more effective than posters in improving students' explanatory text writing skills.